EzrA promotes Z-ring formation through interaction of its QNR motif with FtsA - Li, Tingting; Liu, Xiujian; Zhang, Liangsheng; Li, Haotian; Ni, Minghui; Zou, Wenjin; Liang, Menglei; Gong, Ruotong; Hu, Qiao; Zhao, Lelin; Hu, Zhe; Li, Lu; et al. (Journal of bacteriology, 2025)
Bacteria replicate through binary fission in which the FtsZ-ring positioning and assembly is a crucial process requiring precise spatial and temporal regulation. However, the mechanism of this process remains largely unknown, especially in ovoid-shaped bacteria, such as Streptococci, in which many members are important human and animal pathogens. In this study, we characterize the critical role of the cell division regulator EzrA in the formation of the Z-ring. Our data reveal a model in which EzrA interacts through its QNR motif with FtsA to be properly localized to the septum so as to facilitate the positioning and formation of the Z-ring of Streptococcus suis . This regulatory mechanism could be conserved in Firmicutes . This research provides insights into the regulation mechanism of the Z-ring formation and will contribute to the understanding of the cell division process in Streptococci .